2014
DOI: 10.1097/jom.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Dietary Inflammatory Index With Inflammatory Indices and Metabolic Syndrome Among Police Officers

Abstract: Objectives To determine whether the dietary inflammatory index (DII) is associated with inflammatory or metabolic biomarkers and metabolic syndrome (MetSyn) among police officers. Methods Cross-sectional data from the Buffalo Cardio-Metabolic Occupational Police Stress study were derived from saliva and fasting blood samples, anthropometric measurements, long-term shiftwork histories, and demographic, stress/depression, and food frequency questionnaires. MetSyn was defined using standard criteria. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
289
10
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 293 publications
(317 citation statements)
references
References 22 publications
(29 reference statements)
13
289
10
5
Order By: Relevance
“…In terms of occupational exposure, our observations support the previous studies highlighting the potentially worrying effects of night shift work schedules on employee health [15, [40][41][42][43][44][45]. We demonstrate that even though that the RSW workers were significantly younger, thinner, and had a lower prevalence rate of preexisting health abnormalities than their coworkers involved in DW works (Table 1) at baseline, they showed increased MSC, and lower presence of decreased MSC (Table 2 and 3, Figure 1) after 5 years.…”
Section: Metabolic Syndrome Component Count and Shift Work O R I G Isupporting
confidence: 81%
“…In terms of occupational exposure, our observations support the previous studies highlighting the potentially worrying effects of night shift work schedules on employee health [15, [40][41][42][43][44][45]. We demonstrate that even though that the RSW workers were significantly younger, thinner, and had a lower prevalence rate of preexisting health abnormalities than their coworkers involved in DW works (Table 1) at baseline, they showed increased MSC, and lower presence of decreased MSC (Table 2 and 3, Figure 1) after 5 years.…”
Section: Metabolic Syndrome Component Count and Shift Work O R I G Isupporting
confidence: 81%
“…Prior studies have shown the DII to be significantly and positively associated with several inflammatory biomarkers such as blood IL-6 (6,8,26,43) and CRP (6,24,43) concentrations. In line with our findings, in a cohort of US women, the DII was associated with all-cause, cancer, and CVD mortality (30).…”
Section: Discussionmentioning
confidence: 99%
“…The autonomous consequences of lifetime shift work lead to increased blood pressure [79,80]. The intake by shift workers of more pro-inflammatory diets compared to day workers [87] contribute to their cardiovascular risk, which may also be increased through additional interrelated psychosocial (difficulties in controlling work hours, decreased work-life balance, poor recovery following work), behavioural (weight gain and smoking) and physiological mechanisms (activation of the autonomic nervous system, inflammation, altered lipid and glucose metabolism with related changes in risks for atherosclerosis, metabolic syndrome and type 2 diabetes). In spite of signs indicating such possible disease mechanisms, however, compelling evidence remains to be elucidated [83].…”
Section: Chronic Somatic Health Effectsmentioning
confidence: 99%